Anterior Vaginal Wall Endometrioma: Case Report - Ali Acar; Havvanur Çalışkan; Şeyma Çiçek; Arife Ebru Taşcı; Emine Türen Demir; Sıtkı Özbilgeç (Genel Tıp Dergisi, 2022)
ABSTRACT A 46-year-old woman was referred to gynecology for the assessment and treatment of an anterior vaginal wall cyst. The preoperative physical examination and transvaginal USG of the pelvis were most consistent with the presence of a bladder cyst. Following the excision of the cyst wall, the patient was diagnosed with an endometrioma in the anterior part of the vagina. This case emphasizes difficulties in the identification of endometriosis in the vagina and other uncommon places, potential processes of disease progression, and recommended therapies.